Auxin and Ribonucleic Acid Synthesis in Pea Stem Tissue as Studied by Deoxyribonucleic Acid-Ribonucleic Acid Hybridization - Thompson, William F. (1971)
The ability of auxin to alter gene transcription in pea (Pisum sativum L.) stem tissues has been investigated by means of DNA/RNA hybridization-competition techniques. In order to obtain reproducible hybridization with total nucleic acid preparations from plants it was found necessary to remove interfering substances, probably polysaccharides; this was accomplished by methoxyethanol extraction and precipitation with cetyltrimethylammonium bromide. When purified in this fashion, plant nucleic acids could be made to form hybrids which showed both species specificity and high thermal stability. No change in hybridizable RNA of stem sections in response to auxin could be detected over a 2- to 24-hour period, regardless of the auxin level employed. In contrast, when large doses of auxin were applied to intact pea seedlings, definite changes in the hybridizable RNA of stem tissue were detected both 8 and 24 hours after treatment. Many of the 2,4-D-induced species of RNA which were present at 24 hours were also present at 8 hours. Sections apparently lack a factor needed for the manifestation of the auxin effect on RNA synthesis. Since the hybridization assay employed does not measure all cellular RNA, it is still possible that certain RNA species may be synthesized in sections in response to auxin. However, the auxin promotion of cell elongation in such sections is clearly not associated with changes in hybridizable RNA such as have been reported for several hormonal responses in animal systems.